Design and verification of serial interface engine module in usb standard - Trần Đức Sang; Nguyễn Văn Thành Lộc; Trần Quốc Tấn; Trần Thị Quỳnh Như; Huỳnh Hoàng Hà; Đỗ Duy Tân (Journal of Technical Education Science, 2021)
This paper presents a design and verification of a Serial Interface Engine (SIE) module in the USB 2.0 standard based on FPGA technology. The SIE unit receives data sent from the Central Processing Unit (Central Processing Unit or CPU) and passes it to the Universal Transceiver Macrocell Interface (UTMI). At the sender, the data is converted from parallel to serial, then passed through the error control encoder and the channel encoder before being transmitted over the channel. At the receiver, on the contrary, after going through the channel decoder and the error control decoder, the serial data is converted back to parallel. By means of various simulations, we show that the operation of the designed SIE module fully meets the technical requirements.